A CRITICAL DISCOURSE ANALYSIS OF THE POLICE NEWS STORY FRAMING IN TWO EGYPTIAN NEWSPAPERS BEFORE JANUARY 25 REVOLUTION - Mahfouz, Adel Refaat (European Scientific Journal, ESJ, 2013)
The current study aims to analyze the linguistic structure of the framing of some news stories related to police published in two Egyptian newspapers before January 25 Revolution, one is a totally state-controlled and served as official information outlet “Al-Gomhuria”, and the other is independent “Al-Dostour”. They have been chosen because of their status and because of their political influence. The present study is done via a Critical Discourse Analysis(CDA) perspective in order to explore the scope and nature of the two newspapers’ ideologies, i.e. for or against the former regime and how the reporters’ intervention is used in framing the news stories to make readers understand them in the way intended by the producer of the text. This intervention manifests itself vigorously in the way propositions are constructed, combined, and sequenced and at some linguistic levels such as lexis, syntax, semantics, and pragmatics. Nevertheless, such linguistic features, as Gerbener (1964: 78) argues, "are not themselves of profound and direct significance rather [….] that the nature and consequences of these elements and characteristics can be best understood if content is viewed as bearing the imprint of social needs and uses." For this, some news stories from the two newspapers were selected and analyzed. The study shows how language is used in constructing certain ideologies and how these ideologies exercise a great deal of power in shaping the Egyptian reader’s interpretation of the given facts. The perspectives presented tended to be in line with the beliefs held by the two newspaper’s target audiences.